Penguatan Moderasi Beragama Dan Wawasan Kebangsaan Bagi Guru Ngaji Dan Kiai Kampung Di Kepulauan Gili Iyang Sumenep - Rasuki Rasuki; Mukhlis Mukhlis (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
Radicalism is an action that leads to terrorist behavior and important problem for Indonesian Muslims today. These two issues have caused Islam to be labeled as terror religion and Muslims are considered to favor the path of holy violence to spread their religion. This service was carried out among Koran teacher and village kiai at Gili Iyang Island, Sumenep, Madura with the aim of providing an understanding of religious moderation, strengthening the spirit of nationalism and love for the country and rejecting all forms of radicalism. Because recently quite a few Koran teachers and village kiai have been exposed to violence, discrimination, anti-socialism and even leading to radicalism. The approach used in this service is research-based with a Participatory Action Research model. The activity steps include planning, acting, observing and reflecting. The service team focused on directly providing information to Koran teachers and village kiai about strengthening religious moderation in Gili Iyang Island, Sumenep, Madura. The results of this service can form Koran teachers and village kiai who have moderate views regarding their religion and citizenship, especially in social life in society